STREPTOCOCCUS PNEUMONIAE MOLECULAR EPIDEMIOLOGICAL FEATURES IN CHILDREN OF KRASNOYARSK REGION - I. N. Protasova; N. V. Bakhareva; O. V. Peryanova; T. A. Yelistratova; M. V. Koval (Бюллетень сибирской медицины)
The purpose of the research was to estimate the prevalence of Streptococcus pneumoniae nasopharyngeal carriage in 250 children aged under 5 years and 215 school-aged children in Krasnoyarsk Region, and also investigate molecular epidemiological features of the strains circulating inKrasnoyarsk city and in Krasnoyarsk Region. This study is carried out for the first time in the region and provides a foundation for the choice of optimal vaccination strategy of pneumococcal disease.S. pneumoniae identification was carried out using culture method as well as PCR (revealing of cpsA gene), serotypes were determined with PCR (according to CDC protocol).The prevalence of S. pneumoniae carriage in under-five children was 51,6% with predominated pneumococcal serotypes 23F, 19F and 6В; most of these strains (up to 90%) belonged to those included in pneumococcal vaccines which are permitted for use in Russian Federation; the greatest conformity was observed in 13-valent conjugated vaccine. In school-aged children the S. pneumoniae prevalence was 12,1% with predominated pneumococcal serotypes 6В, 9VA and 15АF, most of these strains (up to 60%) belonged to those included in approved pneumococcal vaccines.Considering high level of S. pneumoniae carriage in children under 5 years in organized groups and unorganized children from families with two or more children it is necessary to carry out vaccine prevention of pneumococcal diseases with of 13-valent pneumococcal conjugated vaccine application.